Pengaruh Pakan Tambahan Berupa Ampas Tahu Dan Limbah Bioetanol Berbahan Singkong (Manihot utilissima) Terhadap Penampilan Sapi Bali (Bos sondaicus) - dwi dedeh kurnia sari (Buletin Peternakan, 2016)
This study was aimed to observe the performance of Bali cattle given additional feed of tofu waste, solid and liquid waste of bio-ethanol made from cassava. Six male Bali cattle with body weight of 190- 230 kg were used. The design of this study was a 3x3 Latinsquare with cross over pattern. The 3 treatments were included feeding DM 3% of the body weight, consist of treatment A : forage and additional feed from tofu wastes 2 kg, 200 g of solid waste and liquid wastes given 100 ml per day, treatment B : forage given daily and additional feed was given once every two days, and treatment C : only forage. The measured variables were (1) feed consumption, (2) daily weight gain (ADG), (3) feed conversion. The results are that the effect of provision of additional feed highly a real and tangible feed intake (P<0.05), ADG (P<0.01), and feed conversion (P<0.01). Average of feed consumption (kg DM-1day-1) for A, B, C were 6.97; 6.92; 6.12, respectively. Average of ADG (kg head-1day-1) for A, B, C were 0.64, 0.50, and 0.10, respectively. Average of feed conversion for treatment A, B, and C were 10.94, 14.00, and 64.00, respectively. We conclueded that additional feed can increase feed consumption, body weight and give high feed conversion. It can be suggested there should be more research on additional levels of solid waste and waste liquid bio-ethanol.